Divergência genética entre árvores matrizes de Ceiba speciosa St. Hil. para características de frutos e sementes - Roveri Neto, Antonio [UNESP] (2014)
Ceiba speciosa St. Hil. is a tropical tree species of the Malvaceae family, which in adulthood, the tree may exceed 20 meters in height and 120 cm in diameter at breast height. Reproduction has mixed, predominantly outcrossing. Its main pollinators are birds, insects and bats. Its wood can be used in industry for making canoes, troughs, furniture, model airplanes, crates and production of pulp; their seed cotton is widely used for filling pillows, blankets and pillows. The species has great importance in the recovery of degraded ecosystems. The present study aimed to evaluate the genetic divergence among mother trees of Ceiba speciosa, from characters of fruits and seeds. Fruits and seeds of 36 mother trees of C. speciosa were collected, determining in five fruits per array diameter, length, fresh weight and dry weight and number of seeds per fruit and 100 seed (5 replicates of 20 units), the length, diameter and weight of 100 seeds. Also, four replicates of 25 seeds per mother tree were subjected to germination test, conducted at 27 º C for 21 days in substrate blotter, by assessing the percentage of seeds with radical protrusion and the germination speed index. The seed quality was evaluated by accelerated aging test conducted at 45 ° C for 72 hours, electrical conductivity conducted with four replications of 40 seeds soaked in 75 mL of deionized water at 25 ° C for 24 h by the submersion test in which the seeds of the same electrical conductivity test were kept in this solution for 120 h. After the EA and submersion test, seeds were subjected to germination test at 27 º C for 10 days. Data were subjected to analysis of variance and comparison of means by the Scott-Knott test, estimating also the genotypic determination coefficient, repeatability and correlation among traits. The genetic divergence among mother trees was obtained by the method of Ward and optimization Tocher, from the average Euclidean distance between pairs ...